Sejarah Perkembangan Akuntansi di Indonesia - Salamah, Rizqi; Umi Fikriyah; Kirana Mahardhika R.; Nur Rohmah Hidayati; Gunawan Aji (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
The history of the development of accounting systems is closely linked to the development of knowledge and technology, with accounting practices functioning as a buffer against the needs of society and the corporate environment in the current period of globalization. This research uses research sources from relevant journals. As part of social science, the emergence of accounting science begins with accounting practices in socio-economic life. The emergence of accounting started in Europe, then developed in Indonesia, which was divided into 4 eras, accompanied by technological developments. Accounting plays a role in national economic development with various professions in the accounting field.